MANĀHIJU NAMŪDẖAJIYATU LILTÃʿALŨMI LITAḤ̊SĪNI DĀFIʿĪÃẗI AL-ṬHULLÃBI FII IKTISĀBI AL-LUGẖATI AL-ARABIYYATI: مناهج نموذجية للتعلم لتحسين دافعية الطلاب في اكتساب اللغة العربية - Muhammad Bachtiar Dwi Surya (Tarbiyah Faculty of Ibrahimy University Ibrahimy University, Situbondo, Indonesia, 2025)
This study aims to analyze the learning model approach in improving students' Arabic learning motivation in the Zaid Bin Tsabit unit, Nurul Jadid Islamic Boarding School, Probolinggo. Arabic has a strategic position in Islamic education, but students' learning motivation is often low due to less varied learning methods and limited teacher-student relations. The Islamic boarding school environment as a center for religious education needs to present adaptive and contextual learning strategies. This study uses a qualitative descriptive approach with observation techniques, in-depth interviews, and documentation. Data are analyzed interactively through reduction, presentation, and verification to explore the findings in depth. The results of the study indicate that the teacher's personal and relational approach plays an important role in building supportive and inclusive relationships, thus encouraging student interest; Varied and innovative learning methods such as taqdimul qissoh, khitobah, and qira'atul syi'ir are able to enrich vocabulary, train speaking courage, and improve text comprehension; and the need to strengthen teacher capacity through pedagogical training and the provision of extracurricular activities to support learning motivation. This study contributes to the development of practice-based Arabic language learning strategies that are relevant to students' spiritual and academic needs, and recommends further studies with a mixed approach in diverse pesantren contexts.